Failure strength of human vertebrae: Prediction using bone mineral density measured by DXA and bone volume by micro-CT - Perilli, E.; Briggs, Andrew; Kantor, S.; Codrington, J.; Wark, J.; Parkinson, I.; Fazzalari, N. (Elsevier Science, 2012)
Significant relationships exist between areal bone mineral density (BMD) derived from dual energy X-ray absorptiometry (DXA) and bone strength. However, the predictive validity of BMD for osteoporotic vertebral fractures remains suboptimal. The diagnostic sensitivity of DXA in the lumbar spine may be improved by assessing BMD from lateral-projection scans, as these might better approximate the objective of measuring the trabecular-rich bone in the vertebral body, compared to the commonly-used posterior–anterior (PA) projections. Nowadays, X-ray micro-computed tomography (µCT) allows non-destructive three-dimensional structural characterization of entire bone segments at high resolution. In this study, human lumbar cadaver spines were examined ex situ by DXA in lateral and PA projections, as well as by µCT, with the aims (1) to investigate the ability of bone quantity measurements obtained by DXA in the lateral projection and in the PA projection, to predict variations in bone quantity measurements obtained by µCT, and (2) to assess their respective capabilities to predict whole vertebral body strength, determined experimentally. Human cadaver spines were scanned by DXA in PA projections and lateral projections. Bone mineral content (BMC) and BMD for L2 and L3 vertebrae were determined. The L2 and L3 vertebrae were then dissected and entirely scanned by µCT. Total bone volume (BVtot=cortical+trabecular), trabecular bone volume (BV), and trabecular bone volume fraction (BV/TV) were calculated over the entire vertebrae. The vertebral bodies were then mechanically tested to failure in compression, to determine ultimate load.The variables BVtot, BV, and BV/TV measured by µCT were better predicted by BMC and BMD measured by lateral-projection DXA, with higher R2 values and smaller standard errors of the estimate (R2 = 0.65–0.90, SEE = 11%–18%), compared to PA-projection DXA (R2 = 0.33–0.53, SEE = 22%–34%). The best predictors of ultimate load were BVtot and BV assessed by µCT (R2 = 0.88 and R2 = 0.81, respectively), and BMC and BMD from lateral-projection DXA (R2 = 0.82 and R2 = 0.70, respectively). Conversely, BMC and BMD from PA-projection DXA were lower predictors of ultimate load (R2 = 0.49 and R2 = 0.37, respectively). This ex vivo study highlights greater capabilities of lateral-projection DXA to predict variations in vertebral body bone quantity as measured by µCT, and to predict vertebral strength as assessed experimentally, compared to PA-projection DXA. This provides basis for further exploring the clinical application of lateral-projection DXA analysis.